Kuyper"s sphere sovereignty and the restriction on building worship places in Indonesia - Intan, Benyamin F. (HTS teologiese studies, 2022)
The Indonesian Constitution guarantees the freedom of Indonesian citizens to worship according to their religion. In reality, however, the Indonesian government had issued regulations that restrict the building of worship places, which is one way of expressing religious freedom. These regulations, being trapped in the discourse of the politicisation of religion and the religionisation of politics, are contradictory to the aspirations of the founding fathers as expressed in the Indonesian Constitution. This article seeks to deal with this problem by conducting a critical and reflective study on religion–state relations, particularly on the concept of sphere sovereignty proposed by Abraham Kuyper. This study employed the content analysis method. The study demonstrates that this concept, when applied to the Indonesian situation, would prove helpful in restoring normative leadership to Indonesian politics and would enable it to align itself with the values of the Indonesian Constitution. The study also recommends a number of practical strategies in protecting religious freedom and rights in Indonesia, especially with regard to the restrictions on building worship places.Contribution: The study of the concept of Kuyper’s Sphere Sovereignty can be helpful in restoring normative leadership to Indonesian politics and would enable it to align itself with the values of the Indonesian Constitution and allow religion to fulfil its responsibility towards the state and the state towards religion, without being trapped in the discourse of the politicisation of religion and the religionisation of politics.